2022
DOI: 10.1371/journal.pone.0264220
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a cellular host response test to risk-stratify suspected COVID-19 patients in the Emergency Department setting

Abstract: Objective Assess the IntelliSep Index (ISI) for risk stratification of patients presenting to the Emergency Department (ED) with respiratory symptoms suspected of COVID-19 during the pandemic. Methods An observational single-center study of prospective cohort of patients presenting to the ED during the early COVID-19 pandemic with respiratory symptoms and a CBC drawn within 4.5 hours of initial vital signs. A sample of this blood was aliquoted for performance of the ISI, and patients were followed for clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The ISI is pathogen agnostic test, providing rapid risk stratification independent of the pathogen, as suggested by the ISI’s ability to risk stratify patients early in the COVID-19 pandemic ( 25 ). A list of potential pathogens identified through various diagnostic methods is presented in S1-Table 6 ( http://links.lww.com/CCX/B289 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ISI is pathogen agnostic test, providing rapid risk stratification independent of the pathogen, as suggested by the ISI’s ability to risk stratify patients early in the COVID-19 pandemic ( 25 ). A list of potential pathogens identified through various diagnostic methods is presented in S1-Table 6 ( http://links.lww.com/CCX/B289 ).…”
Section: Discussionmentioning
confidence: 99%
“…Details of performing the IntelliSep test ( 20 ) can be found in the Supplemental Material ( http://links.lww.com/CCX/B289 ). The IntelliSep result is reported as the ISI, a single number ranging from 0.1 to 10.0, divided into three prespecified interpretation bands using limits of less than equals to 4.9 (band 1) and greater than or equal to 6.3 (band 3), with band 2 intervening ( 25 ).…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we have demonstrated the performance of the IntelliSep test and its corresponding ISI as an early diagnostic test for sepsis and in risk-stratifying patients with signs or suspicion of infection in the emergency department [ 30 , 32 ]. The findings in this study provide evidence to support a connection between the biophysical measurements observed in the IntelliSep test and biological phenomena occurring during leukocyte activation in a dysregulated host response to infection and sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…The test yields an IntelliSep Index (ISI) in under ten minutes, a score between 0.1–10.0 that is stratified into three discrete interpretation bands based on probability of sepsis: Band 1, Band 2, and Band 3 [ 30 ]. The diagnostic performance of the IntelliSep test when applied to patients presenting to the ED with signs or suspicion of infection was previously evaluated in several clinical studies [ 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Once applied to a standardized population, the results of a diagnostic could be more easily applied in protocolized care and/or care pathways. Integration of a sepsis diagnostic such as IntelliSep into clinical management could potentially impact a variety of aspects in sepsis care including patient outcomes, resource utilization, and antimicrobial stewardship [29]. Indeed, a recent costs and consequences modeling study found that the IntelliSep test has the potential to both lower mortality and lower costs of care on average relative to a strategy employing Procalcitonin [30].…”
Section: Discussionmentioning
confidence: 99%